Pruning the Cloud Internal Data Stealing By Treachery Attacks (International Journal of Engineering and Computer Science, 2017)
Cloud Computing is internet based computing provide computing services those are data, application, software and computing, these computing services are delivered to local devices through internet. To store and share personal and business information and access cloud computing enables multiple users. Insider means, users those who have valid authority on the cloud. Attackers are treated as remote users in the security perspective. If the attacker are not a remote users then that should be checked by the security systems. If a authorized user’s access details are stolen by an attacker can enter and access the cloud as a valid user. Distinguishing the real data of user and the attacker data, for this decoy information technology are used in the field of cloud computing. For detection of abnormal access of information and validating whether data access then it confuses the attacker with bogus information.